Respuesta :
answer: x = 11
1. distribute
2. combine like terms
3. add 1x to each side
4. add 42 to each side
5. divide 4 from each side
x=11
1. distribute
2. combine like terms
3. add 1x to each side
4. add 42 to each side
5. divide 4 from each side
x=11
![Ver imagen christine88](https://us-static.z-dn.net/files/dea/d7ae6bce307e4a83c6be6ed86a03c2a8.png)
Answer: X=-3
Step-by-step explanation:
3x-7(4+2x)=-x+2
I would apply the BODMAS rule here by first trying to eliminate the brackets.
To do this I will multiply -7 by (4+2x) =-28-14x. Now the equation becomes 3x-28-14x=-x+2. We collect like terms. 3x-14x+x=2+28. -10x=30. We would divide both sides by -10 to get our X. We have X=-3